Characterization of the Bacteriophage BUCT603 and Therapeutic Potential Evaluation Against Drug-Resistant Stenotrophomonas maltophilia in a Mouse Model - Han, Pengjun; Zhang, Wenjing; Pu, Mingfang; Li, Yahao; Song, Lihua; An, Xiaoping; Li, Mengzhe; Li, Fei; Zhang, Shuyan; Fan, Huahao; Tong, Yigang (Frontiers in Microbiology, 2022)
Stenotrophomonas maltophilia (S. maltophilia) is a common opportunistic pathogen that is resistant to many antibiotics. Bacteriophages are considered to be an effective alternative to antibiotics for the treatment of drug-resistant bacterial infections. In this study, we isolated and characterized a phage, BUCT603, infecting drug-resistant S. maltophilia. Genome sequencing showed BUCT603 genome was composed of 44,912 bp (32.5% G+C content) with 64 predicted open reading frames (ORFs), whereas no virulence-related genes, antibiotic resistant genes or tRNA were identified. Whole-genome alignments showed BUCT603 shared 1% homology with other phages in the National Center for Biotechnology Information (NCBI) database, and a phylogenetic analysis indicated BUCT603 can be classified as a new member of the Siphoviridae family. Bacteriophage BUCT603 infected 10 of 15 S. maltophilia and used the TonB protein as an adsorption receptor. BUCT603 also inhibited the growth of the host bacterium within 1 h in vitro and effectively increased the survival rate of infected mice in a mouse model. These findings suggest that bacteriophage BUCT603 has potential for development as a candidate treatment of S. maltophilia infection.